2008
DOI: 10.1038/mt.2008.104
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulate Ocular Neovascularization

Abstract: In this study, we used ischemia-induced retinal neovascularization (NV) as a model to investigate the possible role of microRNAs in a clinically important disease process. Microarray analysis demonstrated seven microRNAs (miR-106a, -146, -181, -199a, -214, -424, and -451) that were substantially increased and three microRNAs (miR-31, -150, and -184) that were substantially decreased in ischemic retina. Potential targets for the upregulated microRNAs were not identified, but bioinformatic analysis suggested tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
158
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(166 citation statements)
references
References 46 publications
8
158
0
Order By: Relevance
“…Our findings of miR-150 suppression of vascular EC function is consistent with previous reports of miR-150 in regulating B-cell proliferation, development, and differentiation (22)(23)(24) and EC differentiation and vasculogenesis by targeting ZEB1 in human embryonic stem cells (25). A previous study identified multiple miRNAs substantially regulated in ischemic mouse retinas (26), yet the cell-specific roles of these miRNAs in the pathogenesis of neovascular eye diseases were not clear. In addition, several highly expressed miRNAs were identified in human ECs, including miR-126, miR-221/222, miR-21, the let-7 family, the miR-17∼92 cluster, and the miR-23∼24 cluster (27,28).…”
Section: Discussionsupporting
confidence: 82%
“…Our findings of miR-150 suppression of vascular EC function is consistent with previous reports of miR-150 in regulating B-cell proliferation, development, and differentiation (22)(23)(24) and EC differentiation and vasculogenesis by targeting ZEB1 in human embryonic stem cells (25). A previous study identified multiple miRNAs substantially regulated in ischemic mouse retinas (26), yet the cell-specific roles of these miRNAs in the pathogenesis of neovascular eye diseases were not clear. In addition, several highly expressed miRNAs were identified in human ECs, including miR-126, miR-221/222, miR-21, the let-7 family, the miR-17∼92 cluster, and the miR-23∼24 cluster (27,28).…”
Section: Discussionsupporting
confidence: 82%
“…Kulshreshtha et al first reported that hypoxia was able to induce expression changes in miRNAs in cells in 2007 (16). Then, a number of studies revealed that the expression profiles of miRNAs also altered following ischemia and hypoxia in certain organs, including the retina, myocardium and hippocampus (17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Shen et al (32) evaluated a later time point (3 d after high O 2 exposure on day 15 vs. 6 and 12 h on day 12 as studied here), when the events that lead to Hif1a and Vegfa up-regulation have already occurred. Shen et al (32) identified the levels of five miR-17 family members (miR-17-5p, miR-20a, miR-20b, miR-106a, and miR106b) increased at this later time point. We also tested the expression levels of all miR members from the miR-17 family at this same time point using a more sensitive and specific approach (quantitative RT-PCR).…”
Section: Low Levels Of Mir-17 Family In the Initial Steps Of The Angimentioning
confidence: 99%
“…In this case, finely tuned and complex biological processes, such as angiogenesis, require the concerted, simultaneous silencing of all miR-17 family members to bias the biological signals that ultimately lead to blood vessel formation. In a previous study, Shen et al (32) investigated miR alterations by microarray analysis using the ROP model. Shen et al (32) evaluated a later time point (3 d after high O 2 exposure on day 15 vs. 6 and 12 h on day 12 as studied here), when the events that lead to Hif1a and Vegfa up-regulation have already occurred.…”
Section: Low Levels Of Mir-17 Family In the Initial Steps Of The Angimentioning
confidence: 99%